ECOLOGICAL CONCERNS IN CHRISTIAN TRADITIONS: REFLECTIONS ON LAUDATO SÍ - A Alangaram (Asian Horizons, 2015)
All Christians believe that God has created the world and God found it good. God expects us to protect and maintain Nature and to be responsible in the use of natural resources and other living beings. The mother earth today is heavily exploited and her existence is constantly threatened. Many of the natural calamities are the result of human irresponsibility, selfishness and greed. Keeping this in mind, in his recent encyclical Laudato Sí, Pope Francis invites all of us for a true conversion and ecological approach based on the reality of our society.